Caracterización socioeconómica y productiva de la Parroquia La Matriz, Cantón Latacunga, provincia de Cotopaxi 2022. - Herrera Achote, Tatiana Paola (2022)
This research focused on the "Socioeconomic and productive characterization of the parish La Matriz of Latacunga Canton, Cotopaxi Province 2022," the main objective was framed in generating reliable information about the life tasks of the inhabitants of the place under study. A survey was applied as a method of research and data collection, the survey was managed with the KoboToolbox application, which generates an excel spreadsheet with diagnostic data. From the results obtained, it has been possible to identify for the social dimension, that there are almost the same number of men (53%) and women (47%), most of them have a secondary education level with 40%, followed by higher education with 29% and 12% who have only completed primary school, the inhabitants have a rented house made up of 3 to 4 people of which 1 to 2 children and older adults live, no disability (physical-mental) was evidenced in the population consulted. Regarding the economic and service dimension, it shows that 57% of those surveyed have their own business, only 4% are dedicated to horticultural production, likewise, they express that getting a job is difficult (64%), there are also problems in the lack of organizations that do not allow an active participation of the inhabitants, One of the positive elements detected is that there are basic services and infrastructure available to all the inhabitants of the parish. Of the problems to be solved, 63% of those surveyed said security, followed by road maintenance (44%), street cleaning (37%), among other aspects to be improved. Finally, for the organizational productive indicator, it is evident that 64% of the surveyed population states that there is insecurity, however, 77% have not suffered any criminal act, the identified problem of insecurity is the assault with 61%. Of the 4% of people who are engaged in horticulture, only 7% have a productive area of 100 to 1000 m2, of these 47% use organic fertilizers obtained from livestock such as pigs and others, and do not use agrochemicals. With these data obtained from the research, it is recommended to manage public policies aimed at strengthening citizen security, strengthening services and quality of life